La estimulación familiar y su incidencia en el desarrollo cognitivo de los niños y niñas de primer año de educación general básica de la unidad educativa particular La Dolorosa de la ciudad de Quito. Periodo lectivo 2013 -2014 - Romero Vinueza, Cristina Michelle (2014)
This thesis makes reference THE FAMILY STIMULATION AND ITS IMPACT ON BASIC GENERAL EDUCATION FIRST GRADE CHILDREN COGNITIVE DEVEPLOMENT “LA DOLORSA” SCHOOL QUITO CITY. PERIOD 2013-2014. The general objective was: To determine the incidence of Family Stimulation in Cognitive Development of Children First year of General Basic Education of the “LA DOLOROSA” school. The methods used for the preparation of this research work were: Scientist, Inductive-Deductive, Descriptive, and Statistical Model. The techniques and instruments used were: Survey aimed at establishing Parent Family stimulation activities performed with their children; and the Test "BAPAE" to assess the Cognitive Development of Children. In the implementation of the survey Parent concludes that: 50% of Parents use verbalization as Family Activity Stimulation, 43% establishes routines, 33% rhythmic and repetitive activities, 31% activities construction, 28% fine coordination, 15% high-energy activities, drama activities and the 9% drama activities. The results of the test "BAPAE" concludes that: 47% children investigated scoring at 74-51 equivalent next Good Very good; 33% scoring at 89-75 equivalent to Very Good; el10% scoring at 95-90 near equivalent to Very Good to excellent; 4% scoring at 49-26 equivalent upcoming Good to Fair; 3% scoring at 50 equivalent of Good.